Urgensi Profesional Guru dalam Perkembangan Kognitif Nara didik - Felia Limbong; Yonatan Alex Arifianto (SIKIP: Jurnal Pendidikan Agama Kristen, 2022)
Teaching and learning process activities in the school environment are referred to as the transfer of knowledge process. This learning process involves students’ cognitive development, while the cognitive development of each student is not at the same level even though they are of the same age. In general, what happens in the learning process, the teacher’s models and techniques in teaching and conveying knowledge are the same for all students. In response to this, the teacher’s professional urgency in student development is very important. This research has the aim of solving the problem of how the professional urgency of teachers in the cognitive development of students. This study uses a descriptive qualitative approach through a literature review. As for the results of this research, that professional teachers are very important in responding to the cognitive development of students who are not the same as every student, professional teachers must pay attention to and understand the cognitive development of each student and the professional of a teacher must continue to be improved and developed so that it is able to meet the needs of students, especially in the cognitive development of students. Thus, the professional urgency of teachers in the cognitive development of students is necessary for the continuity of the learning process to be more effective and efficient in meeting the cognitive needs of each student.  AbstrakKegiatan proses belajar mengajar dalam lingkungan sekolah disebut sebagai proses transfer of knowledge. Proses pembelajaran ini melibatkan kognitif siswa sedangkan perkembangan kognitif setiap siswa tidak sama tingkatannya meskipun memiliki usia yang sama. Secara umum yang terjadi dalam proses pembelajaran tersebut, model dan teknik guru dalam mengajarkan dan menyampaikan pengetahuan sama bagi semua siswa. Dalam menanggapi hal tersebut urgensi profesional guru dalam perkembangan siswa sangat penting. Melalui penelitian ini memiliki tujuan dalam menyelesaikan permasalahan bagaimana Urgensi Profesional guru dalam Perkembangan Kognitif Nara Didik. penelitian ini menggunakan pendekatan kualitatif deskriptif melalui tinjauan pustaka. Adapun hasil dari penelitian ini, bahwa profesional guru sangat penting dalam menanggapi perkembangan kognitif nara didik yang tidak sama pada setiap nara didik, guru yang profesional harus memperhatikan dan memahami perkembangan kognitif pada setiap nara didik dan profesionalitas dari seorang guru harus terus ditingkatkan dan dikembangkan sehingga mampu memenuhi kebutuhan nara didik terutama dalam perkembangan kognitif nara didiknya. Sehingga pada saat guru menyajikan pembelajaran bagi nara didik tidak hanya terpaku pada satu metode pembelajaran saja tetapi guru bisa mengetahui dan menerapkan berbagai metode pembelajaran dalam proses belajar mengajar. Dengan demikian urgensi profesional guru dalam perkembangan kognitif nara didik mutlak untuk di lakukan dalam keberlangsungan proses belajar agar lebih efektif dan efisien dalam memenuhi kebutuhan kognitif setiap nara didik.